Sesquicentennial commemorative volume of the Royal Asiatic Society of Sri Lanka, 1845-1995 - De Silva, G. P. S. Harischandra; Uragoda, C. G.; Royal Asiatic Society of Sri Lanka (Colombo : The Society, 1995)
Contributed articles on varied subjects.
Includes bibliographical references.
Keywords: Royal Asiatic Society of Sri Lanka